INDONESIA EFL TEACHERS’ REFLECTIVE THINKING AND THEIR TEACHING STYLES: EXPLORING POTENTIAL RELATIONSHIP - Dwi, Fadilla Stephanie; Fithriani, Rahmah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Reflective thinking is an important factor that can affect a teacher's effectiveness when teaching in the educational setting. This study aims to investigate the relationship between reflective thinking of EFL teachers in Indonesia and their teaching styles. A descriptive-correlational design was employed in the quantitative research method, and a survey with fifteen EFL teachers from different Indonesian schools was used to collect data. With a correlation of 0.757 and a significance value (sig) of 0.0010.05, the statistical analysis's results demonstrated a strong positive or close to significant relationship between teachers' reflective thinking levels and their teaching styles. Additionally, the percentage of 53.3% indicates that EFL teachers in Indonesia tend to use the "All-round flexible, Adaptable teacher" teaching style when teaching students in English in the classroom. This finding illustrates that Indonesian EFL teachers who exhibit high levels of reflective thinking tend to have more effective teaching styles. Suggestions for future research include in-depth research to understand specific aspects of reflective thinking as it relates to teaching styles.